MANAJEMEN SUMBER DAYA APARATUR SIPIL NEGARA (ASN) DALAM RANGKA REFORMASI BIROKRASI DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH (BKPPD) KOTA PEKALONGAN - Arvia Oktarina; Mochammad Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Achieving the welfare of the people in a region is determined by many factors in which one of them is the professional performance of the Civil State Apparatus in the area. The number of Corruption, Collusion, and Nepotism (KKN) cases that happened lately proves that the performance of employees has not been maximized. This fact relates to how the Management of Human Resources is running in an area. Human Resource Management still needs improvement to reform the Bureaucracy in order to actualize the professionalism, transparency, and accountability. The implementation of Bureaucratic Reform should also starts from improving the quality of Human Resource management.The research method used in this research is descriptive qualitative. To get information of research data, the writer used purposive sampling. As in common qualitative research, the author used in-depth interview method (in depth interview) with informants who was related and perceived as having the knowledge to this research.The results show that the management of State Civil State Apparatus Resources (ASN) for Bureaucratic Reform in Regional Agency of Education and Training Employment (BKPPD) ofPekalongan City is in accordance with 8 aspects specified in the regulations covering: Recruitment, Job Analysis, Job Evaluation, Preparation of Standard of Managerial Competence, Individual Assessment based on Competence, Performance Assessment, Human Resource Management Information System, as well as Education and Training. Those have been implemented in accordance with the objectives of the Bureaucratic Reform though there aresome of them which are not yet to be done, such as the evaluation of positions as it is currently being conducted in the early stages by providing the socialization and dissemination of the information form about structural position factors to the position holders.The management of Civil State Apparatus Resourcein this research is appropriate enough with the objectiveof Bureaucratic Reform although there is still one aspect that has not been implemented yet and other aspects that still need to be improved again.